Invasive Fungal Infections in Critically Ill Patients: A Prospective Study from a Tertiary Care Hospital in Bangladesh - Akhtar, Shaila; Anwar, Shaheda; Badhan, Raisa Enayet; Jalil, Rafia Afreen; Saleh, Ahmed Abu (Medicine Today, 2026)
Introduction: Invasive fungal infections (IFI) are common nosocomial infections in immunosuppressed individuals. Method: It was a cross-sectional and observational study. A total of 77 peripheral venous blood samples were collected from clinically suspected IFI patients from the intensive care unit (ICU) of Bangabandhu Sheikh Mujib Medical University (BSMMU). The study was conducted from December 2022 to August 2023. Result: A total of 77 critically ill patients with a high risk of invasive fungal infection (IFI) were classified based on blood culture into three groups: no fungemia (41 patients with proven bacterial sepsis), suspected fungemia (25 patients with negative blood culture), and definite fungemia group (11 patients with culture-proven fungemia). 10/54 presented Candida spp. and 1/54 presented Aspergillus spp. Hospitalization for more than 3 weeks, the use of a central device, persistent thrombocytopenia, and CRP levels were significantly higher in the definite fungemia group compared to the other two groups. In contrast, mechanical ventilation lasting more than 1 week was significantly higher in the definite fungemia group compared with the no fungemia group. IFI was more commonly seen in patients with autoimmune diseases (p = 0.002, odds ratio 10.13, 95% CI: 2.3-44). The majority of cases were from the age group of _60 years, predominantly male. Conclusion: Invasive fungal infection is grossly underreported in critical settings. Early suspicion, thorough investigation, and timely diagnosis may alleviate patients of significant mortality and morbidity. Medicine Today 2026, Vol.38 (1): 32-36